Renal cell carcinoma presents as portal vein thrombosis, a very rare combination - Raad Alhaj Tahtouh (22330108) (2025)
Key Clinical Message Portal vein thrombosis (PVT) can indicate underlying conditions, such as malignancy. A case of PVT was later diagnosed as renal cell carcinoma (RCC), highlighting the need to consider cancer in PVT cases and ensure a comprehensive evaluation. Portal vein thrombosis (PVT) is a rare complication that can arise from various underlying conditions. We present a case report of a patient initially presenting with PVT, which was later diagnosed as renal cell carcinoma (RCC). This case highlights the importance of considering malignancy as a potential cause of PVT and the need for a comprehensive evaluation. Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/ccr3.9220